Characteristics and effectiveness of the face gear with transmission-error-controlled curve considering the path of contact (Effect of assembly and manufacturing errors on transmission error) - Tetsuo INOUE; Syuhei KUROKAWA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2023)
The face gear is a crossed gear similar to a hypoid gear. Owing to its compactness and good assemblability, it is used in geared motors and transmissions for helicopters. Studies on various aspects such as design, processing, and tooth modification methods have been conducted for face gears, which are typically used in fishing reels as spinning reels owing to their easy fabrication and small vibration during reel handle rotation. Because face gears without tooth flank modification are sensitive to assembly errors, the fishing reel sensation becomes unstable during mass production. Therefore, assembling and adjusting face gears to achieve a good fishing reel sensation is time consuming. Previously, tooth flank modification with a transmission error (TE)-controlled curve was used to solve this problem. The TE-controlled curve stabilized the fishing reel sensation for assembly. However, in mass production, the manufacturing error of a pinion and face gear must be considered in addition to the assembly error. In this study, we investigated the assembly and manufacturing errors when the pinion and face gear come in contact. Furthermore, we elucidated the meshing mechanism of face gear pairs under various assembly and manufacturing errors. As a result, it was confirmed that the TE-controlled curve was affected by manufacturing errors only. Moreover, a new interesting finding was obtained regarding the meshing of the face gear with a TE-controlled curve. The TE occurrence ought to be attributed to the pressure angle deviation. Hence, it is probable to replace the main cause of the transmission error with the pressure angle deviation. This consideration is the same for a cylindrical gear pair. The meshing of face gear, which was considered complicated, can be reconsidered as the meshing of a simple cylindrical gear pair. Consequently, we revealed that the TE-controlled curve is significantly useful for considering the meshing and design of a face gear pair, which is an advantageous feature.